The Contribution of Emotional Intelligence to Students’ Prosocial Behavior through Spiritual Intelligence and Parenting Styles - Satrio, Muhammad; Sutoyo, Anwar; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2023)
Low prosocial behavior is indicated by lacking care and harming others both physically and emotionally. Regarding this fact, the present study attempted to analyze the effect of emotional intelligence on students’ prosocial behavior through spiritual intelligence and parenting styles in SMP Muhammadiyah. To do so, a correlational quantitative approach was employed by involving 257 students of grade eight selected using a cluster random sampling technique. Their data were collected using the scales of emotional intelligence, spiritual intelligence, adapted prosocial behavior, and parenting styles compiled by the researchers. Further, the collected data were analyzed using a mediation analysis through Hayes model 6. Results showed that spiritual intelligence could mediate the effect of emotional intelligence on students’ prosocial behavior, while the parenting styles could not mediate the effect of emotional intelligence on students’ prosocial behavior. Moreover, the implications and limitations of this study are presented in the discussion session.